The Relation between Assertiveness and Romantic Relationship Satisfaction Among College Students in Emerging Adulthood - Olivia, Brigitta; Cahyanti, Ika Yuniar (PROCEEDING SERIES OF PSYCHOLOGY, 2023)
Open communication and mutual understanding between partners are important factors that can provide satisfaction in romantic relationships. This study aims to determine whether there is a relationship between assertiveness and romantic relationship satisfaction in college students in emerging adulthood. The participants of this study were college students aged 18-25 years who were in a romantic relationship for at least 6 months and had never been married. Data were collected using an adaptation of The College Self-Expression Scale and the Relationship Assessment Scale. Data analysis was conducted with a non-parametric correlation test using the Spearman’s correlation coefficient in the IBM SPSS 25 for windows program. From the results of data analysis, the correlation value between assertiveness and romantic relationship satisfaction is 0.995 with a p<0,05. The results of this study indicate the potential to intervene and support the development of healthier relationship patterns before individuals enter the marriage stage.